Multiple job-holding: Career pathway or dire straits? - Konstantinos Pouliakas; Wieteke S. Conen (IZA World of Labor, 2023)
Multiple job-holding, or "moonlighting", is an important form of atypical employment in most economies. New forms of work, driven by digitalization, may enable its future growth. However, many misconceptions exist, including the belief that multiple job-holders are only low-skilled individuals who moonlight primarily for financial reasons, or that the practice increases during economic downturns. Recent literature highlights the significant links between moonlighting and job mobility. Multiple job-holding allows for the development of workers' skills and spurs entrepreneurship.
Keywords: J01; J22; J24; J62; 330; multiple job-holding; job quality; skills; careers; mobility; entrepreneurship